Poetic Realism as Social Critique: Class and Gender Representations in Theodor Storm's Immensee - Hilda Septriani; Genita Cansrina (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2026)
This study analyzes how the elements of poetic realism in Theodor Storm's novella Immensee (1849) function as instruments of social critique representing class inequality and gender relations in nineteenth-century German society. Using a qualitative method, close reading, Miles and Huberman's (1994) interactive analysis model, and a sociology of literature approach, the study examines how literary elements reflect social structures. The findings show that realism, poetic language, and emotional depth function not merely as aesthetic features but as complementary forms of social critique. Realism portrays marriage as an economic transaction that deprives women of autonomy; poetic language, through the water lily metaphor, indirectly criticizes class norms; and restrained emotional depth reflects emotional repression in bourgeois society. These findings demonstrate that Immensee is more than a melancholic love story; it presents Storm's subtle critique of the class and gender structures that undermine the possibility of authentic relationships across class boundaries.